(untitled) (Revista de História Regional, 2025)
This article aims to analyze the discourses regarding the causes of death of an indigenous worker who worked in thinning activities in an apple orchard in southern Brazil in the late 1990s. Through a police investigation that looked into the working conditions to which indigenous workers were subjected, especially in apple and garlic farming in rural areas, it was possible to analyze the discourses of multiple subjects who narrated the events surrounding the worker’s death. Understanding the story of Fág Mág’s death reveals to us how the State, by way of Health and Justice institutions, allows the death of indigenous people through work.